Remodeling of the skeletal muscle and postsynaptic component after short-term joint immobilization and aquatic training - Rocha, Lara Caetano [UNESP] (2020)
Joint immobilization is commonly used as a conservative treatment for osteoarticular and musculotendinous traumas. However, joint immobilization might elicit degenerative effects on the neuromuscular system and muscle atrophy. For this reason, the choice of strategies that mitigate these effects is essential in the post-immobilization period. Therefore, this study aimed to investigate the impact of aquatic training on the morphology of muscle fibers and motor endplates of the gastrocnemius muscle in the post-immobilization period. Male Wistar rats (90 days old) were divided into groups: Sedentary: no procedure; Immobilization: joint immobilization protocol (10 days); Immobilization/non-training: joint immobilization protocol (10 days) followed by four weeks without exercise intervention; Immobilization/training: joint immobilization protocol (10 days) and post-immobilization aquatic training (4 weeks). After the procedures, we quantified the cross-sectional area (CSA), volume and numerical density of different myofibers types, and total and stained area and perimeter of the motor endplate. We demonstrate the following main results: (a) short-term joint immobilization resulted in myofibers atrophy; however, we verified a small change in the postsynaptic component; (b) the period of inactivity after immobilization caused severe changes in the motor endplate (lower stained area, stained perimeter, total area, and total perimeter) and maintenance of muscle atrophy due to immobilization; (c) the prescription of post-immobilization exercise proved to be effective in restoring muscle morphology and inducing plasticity in the motor endplate. We conclude that short-term joint immobilization (10 days) results in atrophy type I and II myofibers, in addition to a decline in the total perimeter of the motor endplate. Besides, the post-immobilization period appears to be decisive in muscle and postsynaptic remodeling. Thus, aquatic training is effective in stimulating adjustments associated with muscle hypertrophy and plasticity of the motor endplate during the post-immobilization period.